2014
DOI: 10.1523/jneurosci.2214-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Attention Fine-Tunes Auditory–Motor Processing of Speech Sounds

Abstract: The earliest stages of cortical processing of speech sounds take place in the auditory cortex. Transcranial magnetic stimulation (TMS) studies have provided evidence that the human articulatory motor cortex contributes also to speech processing. For example, stimulation of the motor lip representation influences specifically discrimination of lip-articulated speech sounds. However, the timing of the neural mechanisms underlying these articulator-specific motor contributions to speech processing is unknown. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 41 publications
6
64
0
Order By: Relevance
“…In line with the embodiment hypothesis, experiments 1-3 found that the identification of spoken syllables engages the articulatory motor system. These findings agree with previous studies (14,(16)(17)(18)(19)(20), demonstrating that speech perception automatically triggers action. However, our findings challenge the causal role of motor simulation in the computation of linguistic structure (29).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In line with the embodiment hypothesis, experiments 1-3 found that the identification of spoken syllables engages the articulatory motor system. These findings agree with previous studies (14,(16)(17)(18)(19)(20), demonstrating that speech perception automatically triggers action. However, our findings challenge the causal role of motor simulation in the computation of linguistic structure (29).…”
Section: Discussionsupporting
confidence: 93%
“…Many previous studies have suggested that the identification of individual speech sounds (e.g., b vs. p) triggers motor simulation (14,(16)(17)(18)(19)(20)28). These findings leave open the possibility that the combinatorial process that forms sound patterns (e.g., syllables such as blog vs. lbog) relies on algebraic rules, i.e., principles that are disembodied and abstract.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They asked participants to make either a semantic or phonological judgement and concluded that PMC is involved in phonological, but not semantic, judgements, demonstrating a lack of participation of PMC in speech comprehension. More recently, Möttönen, Van de Ven, and Watkins (2014) used TMS and MEG to measure the impact of attention on auditory-motor processing. They found that in the absence of a task, TMS to motor cortex resulted in nonspecific modulations of auditory cortex; articulator-specific effects of TMS were only seen during a working memory task.…”
Section: Discussionmentioning
confidence: 99%